The impact of atrial fibrillation burden early post cryoballoon pulmonary vein isolation on long-term freedom from recurrent atrial fibrillation. (19th May 2022) - Musat, D; Milstein, N; Saberito, M; Bhatt, A; Habibi, M; Preminger, M; Sichrovsky, T; Shaw, R; Mittal, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) is the cornerstone of atrial fibrillation (AF) ablation. A three-month blanking period (BP) is commonly used in clinical trials and practice. Early recurrence of AF portends worse ablation long-term outcome; however, the utility of using AF burden (AFB) early post cryoballoon (CB) PVI to predict long-term outcome is unknown. Purpose: To determine, using ECG data acquired by an implantable loop recorder (ILR), the relationship between post-ablation AFB and long-term freedom from AF. Methods: We enrolled consecutive patients with AF who had CB PVI and an ILR. We determined the monthly AFB for the first 3 months post CB PVI and assessed the relationship between AFB and 1-year freedom from AF. We defined 4 distinct AFB groups: (1) 0%, (2) > 0-0.1%, (3) > 0.1-0.5%, and (4) > 0.5%. Results: There were 210 patients (66 ± 9 years; 138 [66%] male; 116 [55%] paroxysmal AF; CHA2DS2-VASc 2.5 ± 1.6). Following a 3-month BP, 101 (48%) patients had a recurrence of AF at 160 ± 86 days post-ablation. An AFB of > 0% over the first 3 months predicted AF recurrence (p < 0.0001, Figure 1). Patients with > 0.5% AF burden after 1st month and any AF after 2nd month post CB PVI have a very high long-term AF recurrence rate (Figure 2). Conclusion: The best long term outcome post CB PVI is seen in pts who have no AF in the first 3 months post ablation. An AFB >0.5% after the first month and any AF after the second month portend ablation failure. These data define a clinical utility of using AFB to risk stratify patients post CB PVI.